Heat loss through the window frames of buildings - Albert Baiburin; Mikhail Rybakov; Nikolai Vatin (Inzhenerno-stroitelʹnyĭ zhurnal, 2019)
The object of investigation is window frames of buildings since they are critical zones in terms of thermal insulation. It was studied how the properties of window frame affect the change in heat flow and temperature fields. It was analyzed the heat loss that depends on a range of structural features of a window frame, such as geometrical, thermal and physical properties of walls, windows, lintels, and joints. An experiment was designed, computer simulation and laboratory tests were conducted. Eight different types of frame units were analyzed. Their finite-element models in the ELCUD software was developed. The laboratory tests proved the adequacy of finite-element models. The comparative results obtained from tests and numerical models were in consistency. We conducted a full factorial experiment and excluded insignificant factors using statistical analysis. Mathematical models of the joint effect of these factors were developed. A detailed analysis of the join effect of factors on the heat loss through the window frame was performed. The results can be used for the energy classification of buildings in use.